2014
DOI: 10.2106/jbjs.m.00769
|View full text |Cite
|
Sign up to set email alerts
|

Distal Femoral Fresh Osteochondral Allografts

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(33 citation statements)
references
References 38 publications
0
29
1
1
Order By: Relevance
“…The study also showed that risk factors affecting the ability to return to sport were age more than 25 years (P = 0.04) and pre-operative duration of symptoms more than 12 mo (P = 0.003). Raz et al [29] reviewed 58 cases of osteochondral allograft transplantation to the distal femur with an average follow up of 21.8 years. 13 of 58 cases required further surgery of graft removal or TKA, and 1 case underwent multiple debridements before above-the-knee amputation.…”
Section: Shell Allograftmentioning
confidence: 99%
See 2 more Smart Citations
“…The study also showed that risk factors affecting the ability to return to sport were age more than 25 years (P = 0.04) and pre-operative duration of symptoms more than 12 mo (P = 0.003). Raz et al [29] reviewed 58 cases of osteochondral allograft transplantation to the distal femur with an average follow up of 21.8 years. 13 of 58 cases required further surgery of graft removal or TKA, and 1 case underwent multiple debridements before above-the-knee amputation.…”
Section: Shell Allograftmentioning
confidence: 99%
“…Colangeli et al [31] - Raz et al [29] Young, active patients Post-traumatic; OCD MFC, LFC 58 58 28 21.8 yr 22%…”
Section: Bipolarmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficacy of osteochondral allograft transplantation (OCA) has already been previously established [ 18 25 ]. However, its application is limited by the need for infectious disease screening, which requires extended allograft storage [ 26 , 27 ]. Long-term in vitro maintenance of osteochondral allograft tissue poses a very big challenge, especially for cell viability.…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 OCA may be used as primary treatment of focal, medium to large cartilage defects that are less amenable to marrow stimulation and in patients not ideally indicated for arthroplasty procedures. 8 , 14 Conversely, significant osteoarthritis or diffuse, nonfocal chondral pathology remains a contraindication to OCA. Symptomatic concomitant pathology such as malalignment (i.e., coronal and rotational), meniscal insufficiency, ligamentous injury, or adjacent compartment chondral disease may be treated simultaneously to optimize clinical outcomes.…”
Section: Techniquementioning
confidence: 99%